The Factors Causing The Emerging of Transactional Politics in The Local Election in East Kalimantan 2005 From The Perspective of Siyasah Syar'iyyah - Ashar, Ashari; Sultan, Lomba Sultan; Rahim, Abdul; Rahman, Abd (al-'adalah, 2020)
This study examines the practice of the Pilkada (Regional election) that took place in East Kalimantan in 2005. The aim is to obtain an overview of the extent to which the democratic process meets the quality standards desired by law and society at large. Based on the findings of the research, the quality standard is not met optimally due to the emergence of several fraudulent practices, one of which is in the form of transactional politics. Transactional politics or what in an Islamic perspective is called risywah (bribery) are strongly prohibited in legislation and haram in Islamic law. However, the reality is that such practices still take place in certain ways, such as gifts, shadaqah, wages, transport fees, and several other ways to get rid of the impression of bribery. This phenomenon occurs due to several factors including 1) weak regulation and law enforcement; 2) weak understanding of politics; 3) weak community ethics; 4) economic factors.